Analisis Normatif terhadap Keterpaduan Prinsip-Prinsip Konstitusional dalam UUD 1945 dengan Rezim Perlindungan Hak Kekayaan Intelektual di Indonesia” - Seri Mughni Sulubara; Riska Riska; Nurhayati Nurhayati; Amrizal Amrizal; Ashari Efendi (Lembaga Pengembangan Kinerja Dosen, 2026)
Intellectual Property Rights (IPR) are the result of human thought that have economic and social value and play a significant role in encouraging creativity, technological innovation, and sustainable national development. IPR protection not only aims to provide legal certainty for creators and rights holders, but also serves as a strategic instrument in strengthening the creative economy. However, low public awareness of the importance of IPR protection and the gap between legal norms and practices in the field result in frequent violations of intellectual works. This study uses a normative-juridical approach combined with a participatory-educational approach, in accordance with the characteristics of community service activities in the legal field. This approach aims to integrate normative legal analysis with legal education activities for the community, thereby producing both conceptual understanding and practical benefits. The results of the activities show a significant increase in public understanding of the relationship between constitutional principles and IPR protection in Indonesia. Through educational activities and legal dialogues, it was revealed that the integration between constitutional principles and the IPR legal system has not been optimal, not only due to limited regulations, but also weak public legal awareness and the application of substantive justice as mandated by the 1945 Constitution. These findings emphasize the importance of integrating constitutional values ​​in the IPR protection system.